2022
DOI: 10.48550/arxiv.2202.00032
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gertsenshtein-Zel$'$dovich effect explains the origin of Fast Radio Bursts

Abstract: We present a novel model that explains the origin of Fast Radio Bursts (FRBs) -short (< 1 s), bright (0.1 − 1000 Jy) bursts of GHz frequency radio waves. The model has three ingredients -compact object, progenitor with effective magnetic field strength around 10 10 Gauss, and GHz frequency gravitational waves (GWs). The energy conversion from GWs to electromagnetic waves occurs when GWs pass through the magnetosphere of such compact objects due to the Gertsenshtein-Zel'dovich effect. This conversion produces b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…For instance, the GWs that we receive on Earth have the energy of the order of 10 20 Jansky [5]. Recently, it was shown that the energy carried by GWs could have observable effects like in Fast Radio Bursts [133].…”
Section: Future Outlookmentioning
confidence: 99%
“…For instance, the GWs that we receive on Earth have the energy of the order of 10 20 Jansky [5]. Recently, it was shown that the energy carried by GWs could have observable effects like in Fast Radio Bursts [133].…”
Section: Future Outlookmentioning
confidence: 99%
“…We provide this reach for the purpose of illustration only; clearly a lot of work needs to be done to probe ultra high-frequency GWs. In additional to the laboratory searches for high-frequency GWs using the inverse Gertsenshtein effect, astrophysical observations of converted electromagnetic signals are also studied in[68,69].…”
mentioning
confidence: 99%